The impact of cataract surgery on tear film physiology: signs and symptoms, progression and treatment - Nuzzi, Alessia; Tibaldi, Davide; Nuzzi, Raffaele (Frontiers in Medicine, 2025)
PurposeThis study aimed to revise data published in the literature on the effects of cataract surgery on tear film characteristics, in relation to personal clinical surgical experience.MethodsA search was undertaken using PubMed (all years). Search terms included ‘cataract surgery’, ‘phacoemulsification’, ‘cataract extraction’, and ‘manual small-incision cataract surgery’, combined at first with ‘ocular surface’ and ‘lacrimal film’. Second, we combined terms as ‘cataract surgery’, ‘phacoemulsification’, ‘cataract extraction’, ‘manual small-incision cataract surgery’ with ‘dry eye disease (DED)’ and ‘dry eye syndrome’. Third, we combined terms such as ‘cataract surgery’, ‘phacoemulsification’, ‘cataract extraction’, and ‘manual small-incision cataract surgery’ with ‘conjunctival sensitivity’ and ‘sensitivity of the conjunctiva’. Finally, we combined terms as ‘cataract surgery’, ‘phacoemulsification’, ‘cataract extraction’, and ‘manual small-incision cataract surgery’ with ‘epiphora’ and ‘excessive tear’. Relevant in-article references not returned in our searches were also considered.ResultsWe analyzed collected data regarding DED characteristics and management of this condition related to cataract surgery. The relationship between ocular surface signs and symptoms and cataract surgery appears to be strong; indeed, TBUT, Schirmer’s test, and OSDI scores are abnormal as early as 2 weeks after cataract surgery; however, there is conflicting evidence concerning the duration of these alterations and the restoration of the preoperative conditions, generally within 6 months after surgery. An increased risk of DED after cataract surgery is associated with pre-existing MGD. The chosen surgical procedure and pre- and postoperative pharmacological management are also key points in determining the extent of postoperative DED. Finally, no remarkable evidence was found regarding the association of “cataract surgery” with “hyperlacrimation” or “conjunctival sensitivity.”ConclusionThe available evidence is discrepant regarding the onset, progression, and management of this condition. However, the association between cataract surgery and the occurrence of DED thereafter is well documented. Multicenter randomized trials are needed to strengthen the already published data, to investigate these divergencies, and to establish diagnostic-therapeutic protocols to manage this condition.